วัสดุบูรณะฟันเรซินคอมโพสิต: ส่วนประกอบ การพัฒนา และการเลือกใช้งาน (DENTAL RESIN COMPOSITE: COMPOSITION, DEVELOPMENT AND SELECTION) - เอกวรพจน์ ปิยะนารถ (วารสารมหาวิทยาลัยศรีนครินทรวิโรฒ สาขาวิทยาศาสตร์และเทคโนโลยี, 2015)
วัสดุบูรณะฟันเรซินคอมโพสิตเป็นวัสดุที่ลอกเลียนลักษณะฟันธรรมชาติได้ดี เนื่องจากมีสีเหมือนฟันสวยงามเป็นที่นิยมและใช้แทนที่วัสดุบูรณะฟันอมัลกัม ถึงแม้ว่าเรซินคอมโพสิตจะมีความแข็งแรงน้อยกว่า แต่ได้รับความนิยมเพิ่มมากขึ้น ทำให้ได้รับการพัฒนาต่อเนื่องมาตลอดระยะเวลากว่า 50 ปี นับตั้งแต่มีการคิดค้นวัสดุประเภทนี้ ปัจจุบันเรซินคอมโพสิตมีคุณสมบัติทางด้านความแข็งแรงและคุณสมบัติในการใช้งานดีขึ้นกว่าเรซินคอมโพสิตในยุคแรก อย่างไรก็ตามการบูรณะฟันด้วยวัสดุเรซินคอมโพสิตยังคงพบปัญหาเรื่องการเสียวฟันหลังอุดฟัน การเกิดฟันผุซ้ำ การแตกหักของคอมโพสิต สาเหตุอาจเนื่องมาจากการหดตัวของวัสดุในขณะที่แข็งตัว ดังนั้นแนวทางการพัฒนาวัสดุนี้จึงมุ่งเน้นเพื่อการแก้ไขปัญหาดังกล่าวร่วมกับการพัฒนาคุณสมบัติทางกล ทางแสง การต่อต้านเชื้อแบคทีเรียและการใช้งานที่สะดวกมากยิ่งขึ้น รูปแบบในการพัฒนามีทั้งการปรับปรุงส่วนประกอบที่สำคัญของคอมโพสิต และการพัฒนาการใช้งานทางคลินิกกับวัสดุประเภทนี้ บทความนี้นำเสนอข้อมูลเกี่ยวกับการพัฒนาวัสดุเรซินคอมโพสิตที่ใช้ในทางทันตกรรม ในช่วงประมาณปี ค.ศ. 2000 เป็นต้นมา ตั้งแต่ชนิดและส่วนประกอบหลัก รูปแบบการพัฒนาวัสดุ และการเลือกใช้งาน คำสำคัญ: วัสดุอุดฟันเรซินคอมโพสิต การพัฒนาวัสดุเรซินคอมโพสิต Dental resin composite is a good tooth mimics restorative dental material. Due to its color looks like the color of the tooth structure, nowsaday it is popular as a material of choice instead of dental amalgam. Eventhough dental resin composite has an infererior mechanical properties compared to dental amalgam, there is an increase using this material. This leads to the continuum development of this material over almost 50 years since it was invented in 1964. Currently, Resin composite has improved both mechanical and esthetic properties compared to the earlier one. However, the postoperative sensitivity, secondary caries and fractured filling still be found for composite restoration. The main cause for this clinical failure is from the polymerization shrinkage of resin composite. Future development for resin composite aim to solve these problems combine with enhancement of both optical, mechanical and other properties such as antibacterial property and manipulation. The ways to reduce polymerization shrinkage are the modification of the formulation of resin composite and clinical technique. This article provides the information about basic composition, types, development, and selection. Keywords: Dental Resin Composite, Development of Resin Composite